Developing Module for Two-Dimensional Course Based on Ethnomathematics for Fourth Grade of Elementary School Student - Dyah Triwahyuningtyas; Novia Eka Mahmuda; Yulianti Yulianti (Al Ibtida: Jurnal Pendidikan Guru MI, 2020)
AbstractThis research was conducted due to the limitation of independent instructional media for students that is based on the curriculum as a companion to mathematics textbooks. Where the textbooks do not connect mathematics with local culture, so that students are less familiar with their culture. Â This research aims to develop a valid, practical, and effective module for two-dimensional course based on ethnomathematics for fourth grade students of elementary school. The model employed in this development research was 4D model proposed by Thiagarajan that consisted of four stages: Define, Design, Develop, and Disseminate. The data analysis was done by using descriptive quantitative and qualitative. The results of this development showed that the module for two-dimensional course based ethnomathematics was valid and feasible; it was stated by the average score obtained from the experts (87.6%). Furthermore, the module developed obtained a positive response from the teacher and students; it obtained an average score of 88.5%. Then, the module was effective to improve student understanding, it obtained an average score of 81.55. Therefore, the module for two-dimensional course based on ethnomathematics is valid, practical, and effective to be used in the learning process.Keywords: two-dimensional shapes, ethnomathematics, developing module.AbstrakPenelitian ini dilatarbelakangi perlu adanya bahan ajar mandiri berupa modul siswa yang sesuai dengan kurikulum sebagai pendamping buku pelajaran matematika. Di mana buku pelajaran matematika yang digunakan kurang menghubungkan matematika dengan budaya lokal, sehingga siswa kurang mengenal budaya yang ada di daerah. Tujuan penelitian ini untuk mengembangkan modul bangun datar berbasis etnomatematika untuk siswa kelas 4 sekolah dasar yang valid, praktis dan efektif. Metode penelitian pengembangan menggunakan model 4D dari Thiagarajan yang terdiri dari empat tahap, yaitu: tahap pendefinisian (define), tahap perancangan (design), tahap pengembangan (develop), dan tahap penyebaran (disseminate). Analisis data dilakukan dengan menggunakan teknik analisis data deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa modul bangun datar berbasis etnomatematika dinyatakan valid oleh para ahli dengan skor rata-rata 87,6%. Penggunaan modul mendapatkan respon yang positif dari guru dan siswa yaitu menunjukkan rata-rata 88,5%. Dengan menggunakan modul tersebut, pemahaman siswa menjadi meningkat dengan nilai rata-rata mencapai 81,55. Sehingga modul bangun datar berbasis etnomatematika praktis dan efektif dalam pembelajaran matematika.Kata kunci: bangun datar, etnomatematika, pengembangan modul.